2021
DOI: 10.1097/tp.0000000000003618
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Society of Transplantation White Paper: Ethical and Legal Considerations for Alcohol and Cannabis Use in Solid Organ Listing and Allocation

Abstract: Alcohol and cannabis use as a contraindication to organ transplantation is a controversial issue. Until recently, patients in Canada with alcohol-associated liver disease were required to demonstrate abstinence for 6 mo to receive a liver transplant. There is no equivalent rule that is applied consistently for cannabis use. There is some evidence that alcohol and cannabis use disorder pretransplant could be associated with worse outcomes posttransplantation. However, early liver transplantation for patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In the last year, consensus recommendations in the United States and internationally have been developed to help ensure consistency in the selection of AH candidates. [29][30][31] Assessing centers' evolving adoption of this guidance will remain a challenge until an oversight mechanism is developed. As an example, we found that nearly 20% of AH candidates had grade 3-4 encephalopathy at listing-an issue that, if also present during the evaluation process, would prevent an accurate psychosocial assessment and be counter to recommended criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In the last year, consensus recommendations in the United States and internationally have been developed to help ensure consistency in the selection of AH candidates. [29][30][31] Assessing centers' evolving adoption of this guidance will remain a challenge until an oversight mechanism is developed. As an example, we found that nearly 20% of AH candidates had grade 3-4 encephalopathy at listing-an issue that, if also present during the evaluation process, would prevent an accurate psychosocial assessment and be counter to recommended criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent litigation in Canada involved an alcohol abstinence period before waitlisting people with alcohol-induced liver failure, in which alcohol use disorder was raised as a basis for the claim that the policy discriminates on the grounds of disability. 50 - 52 …”
Section: Methodsmentioning
confidence: 99%
“…53 However, accommodations in the form of adequate supports may address this risk. 54 At a minimum, jurisdictions should require through laws and regulations that any proposal that may disadvantage a class of people be supported by a robust scientific justification and subject to oversight by groups that include input from potentially impacted stakeholder groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the incentive to qualify for SOT motivates the concealment of substance use. A careful, interprofessional, case-by-case clinical approach to cannabinoid use was recommended in a recently published white paper from the Canadian Society of Transplantation which also provides a thorough ethical analysis [43]. Several US transplantation psychiatry clinicians also recently published mental health-related and SUD-related recommendations regarding cannabinoid use [38 ▪ ].…”
Section: Cannabinoid Usementioning
confidence: 99%